Interrogating human origins : decolonisation and the deep human past - Porr, Martin; Matthews, Jacqueline M. (Abingdon, Oxon ; New York, NY : Routledge, 2020)
"Interrogating Human Origins encourages new critical engagements with the study of human origins, broadening the range of approaches to bring in postcolonial theories, and beginning to explore the decolonisation of this complex topic. The collection of chapters presented in this volume creates spaces for expansion of critical and unexpected conversations about human origins research. Authors from a variety of disciplines and research backgrounds, many of whom have strayed beyond their usual disciplinary boundaries to offer unique perspectives, all circle around the big questions of what it means to be and become human. Embracing and encouraging diversity is a recognition of the deep complexities of human existence in the past and the present, and it is vital to critical scholarship on this topic. This book constitutes a starting point for increased interrogation of the important and wide-ranging field of research into human origins. It will be of interest to scholars across multiple disciplines, and particularly to those seeking to understand our ancient past through a more diverse lens"--
Interrogating and decolonising the deep human past / Martin Porr and Jacqueline M. Matthews -- IMHO : inventing modern human origins / Iain Davidson -- Modern colonial ontologies of the 'more-than-animal' human : provincialising humanism for the present day / Kay Anderson -- Colonialism and narratives of human origins in Asia and Africa / Sheela Athreya and Rebecca Rogers Ackermann -- Primordialising Aboriginal Australians : colonialist tropes and Eurocentric views on behavioural markers of modern humans / Ian J McNiven -- Old flames : rekindling ideas of fire, humanity and representation through creative art practice / Ursula K Frederick -- Orientalism and origins : the search for firsts in the 'Cradle of Civilization' / Allison Mickel -- The beast without : becoming human in the science fiction of H.G. Wells / John McNabb -- The temporality of humanity and the colonial landscape of the deep human past / Martin Porr -- The Far West from the Far East : decolonisation and human origins in East Asia : the legacy of 1937 and 1948 / Robin Dennell -- Interpretative shifts in understanding the prehistoric settlement of the Indian subcontinent : comparing Western and Indian historical perspectives / Parth R Chauhan -- Our earliest ancestors : human and non-human primates of North America / Paulette F Steeves -- "If we are all African, then I am nothing" : hominin evolution and the politics of identity in South Africa / Amanda Esterhuysen -- Naming the sacred ancestors : taxonomic reification and Pleistocene genomic narratives / Jonathan Marks -- Traditional owner participation in genetic research : a researcher perspective / Craig Muller and Joe Dortch.
OCLC-licensed vendor bibliographic record.
Keywords: Human beings -- Origin; Decolonization; Postcolonialism; SOCIAL SCIENCE / Archaeology